Chlorophyllin attenuates the effects of benzo[a]pyrene in human hepatoma HepG2/C3A cells - D´EpiroGláucia Fernanda Rocha; Semprebon, Simone Cristine; Niwa, Andressa Megumi; Marques, Lilian Areal; Biazi, Bruna Isabela; Zanetti, Thalita Alves; Felicidade, Ingrid; Baranoski, Adrivanio; Mantovani, Mário Sérgio (Acta Scientiarum. Biological Sciences, 2023)
Chlorophyllin, a semisynthetic compound derived from chlorophyll, has been a focus in cancer prevention because it exerts important biological activities, such as antigenotoxic, antioxidative and anticarcinogenic activities. The aim of this study was to evaluate the effect of chlorophyllin against benzo[a]pyrene toxicity in HepG2/C3A cells. Cells were co-treated (chlorophyllin plus benzo[a]pyrene) and the cell viability, cell growth kinetics, cell cycle, and apoptosis were evaluated. The mRNA levels of cell cycle and apoptotic genes were analyzed. Our results showed that chlorophyllin reduce the antiproliferative effects of benzo[a]pyrene in a multi-specific manner, restoring the normal distribution of the cell cycle and inhibiting the cell death induced by the xenobiotic. Gene expression analysis showed that benzo[a]pyrene decreased the mRNA levels of genes involved in cell cycle control (cyclins and cyclin-dependent kinases) and apoptosis. Cells co-treated with 200 µM of chlorophyllin and benzo[a]pyrene also showed a downregulation of mRNA levels of the genes, but the expression levels of the gene that encodes to tumor protein p53 were maintained near to control. Thus, chlorophyllin is a good candidate as a chemoprotective agent that mitigates the cytotoxic effects benzo[a]pyrene and, thus, might be a promising tool to prevent liver cancer.